Study on Synthesis and Characterization of Composite Anion Exchange Membrane Based on poly(styrene-co-vinylbenzyl ammonium hydroxide) and poly(vinyl alcohol) - Thi Hong Nhung, Vu; Thi Lan Phuong, Huynh; Huu Tho, Nguyen; Thi Cam Ha, Nguyen; Van Thuc, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2019)
In this study, poly(styrene-co-vinyl benzyl trimethyl ammonium chloride) with different styrene to vinyl benzyl chloride ratio (3:1, 1:1, 1:2) have been synthesized. The formation ofproducts was confirmed by Fourier transform infrared spectrophotometry (FTIR) and nuclear magnetic resonance spectra ( 1 H NMR). Then, anion exchange membranes were prepared by combination of poly(styrene-co-vinyl benzyl trimethyl ammonium hydroxide) and poly (vinyl alcohol) The obtained membranes were evaluated for their own conductivity, anion exchange capacity, and thermal decomposition. The results showed that the anion exchange membrane produced from copolymer with styrene to vinyl benzyl chloride ratio 1: 2 exhibited good hydroxide conductivity of 7 mS/cm, ion exchange capacity was 0.65mmol/g and stability to 200 o C. Keywords Membrane, poly(vinyl alcohol), copolymer, conductivity, fuel cell. References [1] D. J. Kim, C. H. Park, S. Y. Nam, Characterization of a soluble poly(ether ether ketone) anion exchange membrane for fuel cell application, Int. J. Hydrogen Energy 41 (2016) 7649-7658. https:// doi.org/10.1016/j. ijhydene.2015.12.088 [2] J. Fu, J. Qiao, H. Lv, J. Ma, X.-Z. Yuan, H. Wang, Alkali doped poly(vinyl alcohol) (PVA) for anion-exchange membrane fuel cells - Ionic conductivity, chemical stability and FT-IR characterizations, Alkaline Electrochem. Power Sources 25 (2010) 15–23. http://doi.rog/10.1149/ 1.3315169 [3] D. L. Zugic, I. M. Perovic, V. M. Nikolic, S. L. Maslovara, M. P. Marceta Kaninski, Enhanced Performance of the Solid Alkaline Fuel Cell Using PVA-KOH Membrane, Int. J. Electrochem. Sci. 8 (2013) 949-957. [4] Jikihara, R. Ohashi, Y. Kakihana, M. Higa, and K. Kobayashi, Electrodialytic transport properties of anion-exchange membranes prepared from poly(vinyl alcohol) and poly(vinyl alcohol-co-methacryloyl aminopropyl trimethyl ammonium chloride), Membranes (Basel) 3 (2013) 1-15. http: //doi.rog/10.3390/membranes3010001 [5] S. Vengatesan, S. Santhi, S. Jeevanantham, G. Sozhan, Quaternized poly(styrene-co-vynylbenzyl choloride) anion exchange membranes for alkaline water electrolysers, Journal of Power Sources 84 (2015) 361-368. https://doi.org/10.1016/j.jpowsour. 2015.02.118 [6] L. E. Shmukler, N. V. Thuc, and L. P. Safonova, Conductivity and thermal stability of proton-conducting electrolytes at confined geometry of polymeric gel, Ionics 19 (2013) 701-707. https:// doi.org/10.1007/s11581-012-0800-2 [7] D//A. Lewandowski, K. Skorupska, J. Malinska, Novel poly(vinyl alcohol)–KOH–H2O alkaline polymer electrolyte, Solid State Ionics 133 (2000) 265-271. https://doi.org/10.1016/S0167-2738(00) 00733-5 [8] Jun F, Y. Wu, Y. Zhang, M. Lyu, J. Zhao, Novel anion exchange membranes based on pyridinium groups and fluoroacrylate for alkaline anion exchange membrane fuel cells, Int. J. Hydrogen Energy 40 (2015) 12392-12399. https://doi.org/10. 1016/j.ijhydene.2015.07.074 [9] Géraldine M, M. Wessling, K. Nijmeijer Anion exchange membranes for alkaline fuel cells: A review, Journal of Membrane Science, 377(2011) 1-35. https://doi.org/10.1016/j.memsci.2011.04.043.